Utilization of Waste Bricks as a Cement Substitution Material in Concrete Mixture - Fantoni; Yayan Oktiawan; Gunawan; Abi Suar; Delfi Kurnia Zebua (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2023)
Concrete is the main material in building construction. The use of Portland cement as a binder in concrete mixes causes high concrete production costs. Apart from that, cement production also produces high CO2 emissions. Therefore, this research aims to utilize brick waste discarded from the brick industry as a partial substitute for cement in the concrete mixture. The brick powder is sieved to 80 mesh size and then used to replace cement with variations of 0%, 5%, 10%, 15% and 20% based on the weight of the cement. The compressive strength of the concrete was tested at 7, 14 and 28 days. Test results show that the use of brick waste up to 10% can increase the compressive strength of concrete. At 15% and 20% substitution, there was a decrease in the compressive strength of the concrete due to incomplete pozzolanic reaction. So it is concluded that brick waste can be used as a substitute for cement up to 10% in the concrete mixture without reducing its compressive strength. This research can provide solutions for environmentally friendly waste utilization and reduce the use of cement in concrete mixtures.